Indigen Bacteria from Spent Bleaching Earth Waste as A Removal Agent of Fe and Cu - Inike Fratiwi; A Napoleon; Hary Widjayanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The most pollution produced by oil palm factory is Spent Bleaching Earth, because the waste contains residue of oil and dangerous metal that enable bacteria to live hence the research was done to get bacteria of Fe and Cu metal as bioremoval agent. Waste sampling method is random sampling, then purification, selection and potency test. Bacteria that pass potency test on metal containing media are identified and characterized by their genus. The result of the research indicated that the indigenous bacteria genus for good accumulation of Fe metal is Salmonella sp (B7) and for Cu metal is Escherichia sp (B1).